Influenza Vaccine-related Subacromial/Subdeltoid Bursitis: A Case Report - Wright, Alexandra (J Radiol Case Rep, 2019)
Serious side effects of vaccinations are not common, though rare complications can occur. We present a case of one such uncommon side effect, influenza vaccine-related subacromial/subdeltoid bursitis. A 72-year-old female presented with severe shoulder pain following influenza vaccination. The pain persisted for up to two months despite conservative measures, and MRI demonstrated moderate subacromial/subdeltoid bursitis. Vaccine-related shoulder dysfunction includes a range of pathology, from osteonecrosis to bursitis, which will be reviewed in this report. Recognition of infrequent vaccine-related musculoskeletal pathology is important to prevent delay of diagnosis.